2022
DOI: 10.1212/wnl.0000000000200856
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Variability After Cerebrovascular Events: A Possible New Therapeutic Target

Abstract: Blood pressure variability, the variation of blood pressure during a certain period, results from the interaction of hemodynamic, neuronal, humoral, behavioral, and environmental factors. Cerebral autoregulation is impaired in acute cerebrovascular disease. In these patients, increased blood pressure variability may provoke or exacerbate secondary brain injury. In fact, available data showed that increased Blood pressure variability is associated with worse outcomes after acute ischemic stroke, intracerebral h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Some studies suggest more stable nimodipine concentrations with IV formulation [ 27 ] or a lower bioavailability of enteral nimodipine [ 28 ] which was not supported by others [ 29 ]. It is reasonable that continuous IV nimodipine application could smooth blood pressure control and avoid blood pressure fluctuations, which are known to be associated with DCI and poor functional outcome in patients with SAH [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest more stable nimodipine concentrations with IV formulation [ 27 ] or a lower bioavailability of enteral nimodipine [ 28 ] which was not supported by others [ 29 ]. It is reasonable that continuous IV nimodipine application could smooth blood pressure control and avoid blood pressure fluctuations, which are known to be associated with DCI and poor functional outcome in patients with SAH [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Post-stroke BP fluctuations represent a multifactorial and intricate physiological process ( 6 ). Numerous studies have revealed the correlation between preoperative, intraoperative, and postoperative BP levels and clinical outcomes as an crucial clinical factor ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Higher blood pressure variability (BPV) in the setting of both acute ischemic stroke (AIS) and hemorrhagic stroke has been associated with a higher risk of death and recurrent stroke, as well as worse poststroke functional outcomes. [1][2][3][4][5][6][7] However, the relationship between BPV and prognosis is not unique to patients with stroke and has been observed in a variety of acute illnesses. [8][9][10] Among nonstroke intensive care unit (ICU) patients, high BPV has been identified as a risk factor for increased mortality during the ICU stay and after discharge.…”
Section: Introductionmentioning
confidence: 99%